Study of Stomata Characteristics of Plantain and Horn Plants AAB genome - Clemens Sudiyono Narahayaan; Adriana Hiariej; Pieter Agusthinus Riupassa (Jurnal Penelitian Pendidikan IPA, 2022)
The study of stomata characteristics of plantain and horn plants has been carried out. This study aimed to compare the characteristics of plant stomata by plantain and horn banana AAB genome. Therefore, it is possible to find out the similarities and differences in characteristics between plantain and horn banana that have the same genome, including by stomata location, cover cell shape, stomatal type, number of epidermal cells, number of stomata cells, stomata length, stomata width, stomata area, stomata index, and stomatal density. Stomata observations were made by making an incision using the whole mount method. The results obtained were then analyzed descriptively qualitatively by describing the stomata characteristics of the plantain and horn banana plants